2013
DOI: 10.1017/s1751731112002170
|View full text |Cite
|
Sign up to set email alerts
|

Confinement of lactating sows in crates for 4 days after farrowing reduces piglet mortality

Abstract: To reduce mortality among suckling piglets, lactating sows are traditionally housed in farrowing crates. Alternatively, lactating sows can be housed in farrowing pens where the sow is loose to ensure more behavioural freedom and consequently a better welfare for the sow, although under commercial conditions, farrowing pens have been associated with increased piglet mortality. Most suckling piglets that die do so within the first week of life, so potentially lactating sows do not have to be restrained during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 37 publications
3
43
1
1
Order By: Relevance
“…Expectedly, piglet crushing was the main reason causing losses. Using similar farrowing pens with integrated crates as used in this study, Moustsen et al (2013) observed a higher piglet mortality rate in pens where sows were loose-housed throughout the whole lactation period than in those that were crated during the first 4 or 7 days pp; suggesting that crating for just 4 days pp is sufficient to avoid unnecessary crushings. Comparing farrowing crates with free farrowing pens, Hales et al (2014) found greater mortality rates in pens than in crates, even though pen sizes were, at 5.3 to 6.3 m 2 , considerably larger than in this as well as the aforementioned study.…”
Section: Performancementioning
confidence: 62%
See 3 more Smart Citations
“…Expectedly, piglet crushing was the main reason causing losses. Using similar farrowing pens with integrated crates as used in this study, Moustsen et al (2013) observed a higher piglet mortality rate in pens where sows were loose-housed throughout the whole lactation period than in those that were crated during the first 4 or 7 days pp; suggesting that crating for just 4 days pp is sufficient to avoid unnecessary crushings. Comparing farrowing crates with free farrowing pens, Hales et al (2014) found greater mortality rates in pens than in crates, even though pen sizes were, at 5.3 to 6.3 m 2 , considerably larger than in this as well as the aforementioned study.…”
Section: Performancementioning
confidence: 62%
“…Nevertheless, most lactating sows in the developed world are still crated (Barnett et al, 2001). Marchant et al (2000) and Moustsen et al (2013) investigated farrowing systems which represent a compromise between free farrowing and continuous confinement of the sow. In these systems the sows are only crated for the first days pp when the danger of piglet crushing is most serious.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study of confinement of lactating sows, Moustsen et al (2013) housed the animals in a swing-side system. Moustsen et al (2013) showed that piglet mortality Values in a row without a common superscript differ (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%